Platelet P2Y12 inhibiting therapy in adjunct to vascular dose of rivaroxaban or aspirin: a pharmacodynamic study of dual pathway inhibition vs. dual antiplatelet therapy. Issue 7 (30th March 2022) - Galli, Mattia; Franchi, Francesco; Rollini, Fabiana; Been, Latonya; Jaoude, Patrick Abou; Rivas, Andrea; Zhou, Xuan; Jia, Sida; Maaliki, Naji; Lee, Chang Hoon; Pineda, Andres M; Suryadevara, Siva; et al.
Abstract: Aims: Dual pathway inhibition (DPI) by adding a vascular dose of rivaroxaban to a single antiplatelet agent has emerged as a promising antithrombotic strategy. However, in most studies the antiplatelet agent of choice used in adjunct to a vascular dose of rivaroxaban was aspirin, and data on a P2Y12 inhibitor and how this DPI regimen compares with standard dual antiplatelet therapy (DAPT) are limited. Methods and results: This investigation was a substudy analysis conducted in selected cohorts of patients with stable atherosclerotic disease enrolled from a larger prospective, open-label, parallel-group pharmacodynamic (PD) study. We analysed data from 40 patients treated with either clopidogrel- or ticagrelor-based DAPT first, and clopidogrel- or ticagrelor-based DPI thereafter. PD measures explored key pathways involved in thrombus formation and included markers of (1) P2Y12 reactivity, (2) platelet-mediated global thrombogenicity, (3) cyclooxygenase-1 activity, (4) thrombin receptor-activating peptide (TRAP)-induced platelet aggregation, (5) tissue factor (TF)-induced platelet aggregation, and (6) thrombin generation. Compared with DAPT, on a background of the same P2Y12 inhibitor (clopidogrel or ticagrelor), DPI was associated with reduced thrombin generation, increased markers of cyclooxygenase‐1 activity and TRAP-induced platelet aggregation, and no differences in markers of P2Y12 signalling, platelet‐mediated global thrombogenicity, and TF-induced platelet aggregation. In an analysis according to P2Y12 inhibitor type, ticagrelor reduced markers of platelet‐mediated global thrombogenicity, P2Y12 signalling, and rates of high platelet reactivity compared with clopidogrel. Conclusion: Compared with DAPT with aspirin and a P2Y12 inhibitor, the use of a P2Y12 inhibitor in adjunct to a vascular dose of rivaroxaban as part of a DPI strategy is associated with similar effects on platelet-mediated global thrombogenicity but reduced thrombin generation. A DPI strategy with ticagrelor is associated with enhanced antithrombotic efficacy, the clinical implications of which warrant larger scale investigations. Clinical trial registration: ClinicalTrials.gov identifier: NCT03718429.